Efficacy of Brain Training Games on the Cognitive Functioning, Working Memory and Processing Speed of Healthy Individuals: A Meta-Analysis - Fahad Somaa; Azka Khan; Alaa Arafah (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: Brain training games refer to as the activities designed for the stimulation of several cognitive functions. These games could be carried out through different platforms and can be accessed through smart phones, tablets, computers and other gaming devices. Objective: The objective of this meta-analysis is to determine the efficacy of brain training games on the cognitive functioning, processing speed, and working memory of healthy individuals. Methods: The meta-analysis was conducted by carrying out a comprehensive literature search strategy utilizing several relevant databases such as Pub Med, Google Scholar, Scopus, and Web of Science. The filters were applied to each of the databases with reference to the pre-defined eligibility criteria. The filters of language (English), publication year (2000–2024), study design (RCT), population (healthy individuals), and outcome variables (processing speed, memory, and cognitive functioning) were applied to identify the studies relevant to the research topic. Results: A total of 16 studies were selected to include in the review. The findings of the study reported that brain training games have reported statistically significant (P < 0.05) findings from the baseline. Some studies supported the efficacy of brain training games whereas some studies supported the efficacy of aerobic and other exercises over brain training exercises. Conclusion: Brain training games are effective for the improvement of cognitive functions, processing and working memory.